THIOCOLCHICOSIDE-ASSISTED SILVER NANOPARTICLES FOR CONTROLLING WOUND PATHOGENS: IN VITRO ANTIBIOFILM ACTIVITY, PROTEIN AND DNA LEAKAGE AGAINST PSEUDOMONAS AERUGINOSA AND ENTEROCOCCUS FAECALIS - PARIVRAJ PRIYAM; RENU VAJJIRAVELU; ROHIT KUMAR SINGH; DEEPAK NALLASWAMY; SANTHOSHKUMAR JAYAKODI; RAJESHKUMAR SHANMUGAM (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: To synthesize silver nanoparticles (AgNPs) using Gloriosa superba extract and to functionalize with thiocolchicoside, and to evaluate their antibacterial, antibiofilm, protein leakage, cytoplasmic leakage, and time-dependent antimicrobial activities against Gram-positive and Gram-negative bacteria. Methods: Aqueous extract of G. superba was mixed with silver nitrate (AgNO3) to synthesize AgNPs, indicated by a color change from light to dark brown. Ultraviolet-visible (UV-vis) spectroscopy and transmission electron microscopy (TEM) were performed. Antibiofilm activity was measured by optical density (OD) against Enterococcus faecalis and Pseudomonas spp., while protein and cytoplasmic leakage assays assessed membrane damage. Antimicrobial activity and time-kill kinetics were tested against E. faecalis, Escherichia coli, Pseudomonas spp., and Staphylococcus aureus at 25– 100 μg/mL. Results: UV-vis spectra showed a peak at 250–270 nm, confirming nanoparticle formation. TEM images revealed spherical particles. TC-AgNCs reduced biofilm OD from 0.525±0.015 to 0.455±0.005 (E. faecalis) and 0.54±0.015 to 0.46±0.005 (Pseudomonas spp.) at 25–100 μg/mL. Protein leakage increased from 0.34±0.006 to 0.38±0.006, and cytoplasmic leakage from 0.28±0.01 to 0.38±0.01. Antimicrobial activity was observed at 100 μg/mL: Pseudomonas spp. (22.5±1.0), E. faecalis (18.5±0.9), E. coli (16.0±0.8), and S. aureus (18.0±0.9). Time-kill analysis showed a reduction in bacterial counts with increasing concentration and time. Conclusion: TC-AgNCs synthesized using G. superba extract are stable, predominantly spherical, and exhibit strong dose- and time-dependent antibacterial and antibiofilm activity, with membrane-disruptive effects against both Gram-positive and Gram-negative bacteria.